Pharmacokinetics of subcutaneous recombinant methionyl human leptin administration in healthy subjects in the fed and fasting states : regulation by gender and adiposity - Chan, Jean L. (2008)
BACKGROUND: Recombinant human leptin (r-metHuLeptin) has demonstrated efficacy in improving hormonal and metabolic parameters in leptin-deficient states, and it has been suggested that leptin replacement may reverse metabolic adaptations during weight loss iterventions. Pharmacokinetics of subcutaneously administered r-metHuLeptin have been recently published, but whether pharmacokinetic parameters are altered by short-term fasting, adiposity, and/or gender has not yet been evaluated. We sought to characterize pharmacokinetic parameters following subcutaneous r-metHuLeptin administration at a range of physiologic to pharmacologic doses in the fed state and during 3-day complete fasting in lean and obese individuals, including men and women. METHODS: We analyzed pharmacokinetic profiles in 5 lean men, 5 obese men, and 5 lean women following subcutaneous administration of physiologic (0.01 mg/kg), supraphysiologic (0.1 mg/kg), and pharmacologic (0.3 mg/kg) doses of r-metHuLeptin given once in the fed state and once daily during 3-day complete caloric deprivation (fasting). RESULTS: With r-metHuLeptin administration at 0.01 mg/kg, leptin levels ranged up to ~7 ng/ml in lean men, ~20 ng/ml in obese men, and ~30 ng/ml in lean women. There was a significant effect of 3-day fasting to decrease baseline leptin levels, maximal concentration (C(max)), and area under the curve (AUC) (all P<0.0001) and to increase clearance (P<0.001), most prominently in lean men (P<0.0001 across groups). Administration of r-metHuLeptin at 0.1 mg/kg resulted in leptin levels up to ~70 ng/ml in lean men, ~100 ng/ml in obese men, and ~150 ng/ml in lean women. At this dose, there was a similar effect of fasting on the above parameters as well as a decrease in half-life (P=0.02), consistent with increased clearance, but the effect of fasting was overall less pronounced compared with the 0.01 mg/kg dose. With r-metHuLeptin administration at 0.3 mg/kg, leptin levels ranged up to ~150 ng/ml in lean men, ~300 ng/ml in obese men, and ~400 ng/ml in lean women. At this dose, fasting increased clearance to a lesser degree (P=0.046), mainly in lean men, suggesting that the fasting-induced increase in leptin clearance by the kidneys can plateau. Within each group, subjects lost ~3–4 kg of body weight after 3 days of fasting (all P<0.0001), but the amount and time course of weight loss did not differ according to the dose of r-metHuLeptin administered or circulating leptin levels achieved. CONCLUSIONS: Short-term fasting in healthy individuals results in increased clearance of leptin; this contributes to hypoleptinemia, which may serve as a signal to increase energy intake in the setting of caloric restriction. Obese individuals with greater energy stores at baseline have a blunted response to the fasting-induced increase in leptin clearance. Also, women have a differential response to fasting with primarily decreased leptin production rather than increased clearance. These findings and the resulting formulas for calculating doses for r-metHuLeptin administration have important implications for the future therapeutic use of r-metHuLeptin in conjunction with hypocaloric diets for the treatment of obesity.